Limboto Lake Management Model Based on Adaptive Governance - Muh.Firyal Akbar; Franky Djafar; Agri Yani Tolinggi (Borong Newinera Publisher, 2023)
This research aims to analyze motivation and issues, structure and networks between stakeholders in the management of Lake Limboto; and explains how the adaptive model intervenes in the management of Lake Limboto in Gorontalo Regency. This research uses a qualitative approach. Data collection techniques include in-depth interviews, documentation, observation and carrying out Focus Group Discussions (FGD). Data were analyzed using the spiral technique. The results of the research show that the Gorontalo Regency Government from an Adaptive Governance perspective is not yet able/not ready to survive in the face of environmental changes that may occur at any time. The motivation and issues of each stakeholder show a desire to manage and even save Lake Limboto from damage, however, activities are still found in the Lake carried out by the community which actually accelerate the degradation of the Lake environment. The structural pattern in the management of Lake Limboto requires an adaptive model that utilizes the potential resources of each stakeholder, both from the civil sector; Private and Government.